Drosophila Piwi functions downstream of piRNA production mediating a chromatin-based transposon silencing mechanism in female germ line. - Wang, S.H.; Elgin, S.C. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Transposon control is a critical process during reproduction. The PIWI family proteins can play a key role, using a piRNA-mediated slicing mechanism to suppress transposon activity posttranscriptionally. In Drosophila melanogaster, Piwi is predominantly localized in the nucleus and has been implicated in heterochromatin formation. Here, we use female germ-line-specific depletion to study Piwi function. This depletion of Piwi leads to infertility and to axis specification defects in the developing egg chambers; correspondingly, widespread loss of transposon silencing is observed. Germ-line Piwi does not appear to be required for piRNA production. Instead, Piwi requires Aubergine (and presumably secondary piRNA) for proper localization. A subset of transposons that show significant overexpression in germ-line Piwi-depleted ovaries exhibit a corresponding loss of HP1a and H3K9me2. Germ-line HP1a depletion also leads to a loss of transposon silencing, demonstrating the functional requirement for HP1a enrichment at these loci. Considering our results and those of others, we infer that germ-line Piwi functions downstream of piRNA production to promote silencing of some transposons via recruitment of HP1a. Thus, in addition to its better-known function in posttranscriptional silencing, piRNA also appears to function in a targeting mechanism for heterochromatin formation mediated by Piwi.